Unit Hydrograph Modeling using Geomorphological Instantaneous Unit Hydrograph (GIUH) Method - Anantri Sulistyowati; Rachmad Jayadi; Adam Pamudji Rahardjo (Journal of the Civil Engineering Forum, 2018)
Flood forecasting at Wonogiri Reservoir is restricted on the availability of hydrologic data due to limited monitoring gauges. This issue triggers study of unit hydrograph modeling using Geomorphological Instantaneous Unit Hydrograph (GIUH) which is based on Geographic Information System (GIS). Analysis of physical watershed parameters was conducted on Digital Elevation Model (DEM) data using software Watershed Modeling System (WMS) 10.1 and ArcGIS. Nash model and S-curve method were used to process triangular GIUH into hourly Instantaneous Unit Hydrograph (IUH) and Unit Hydrograph (UH) and then was compared with the observed UH of Collins method. A sensitivity analysis was conducted on parameter of RL and Nash-model k. Evaluation of accuracy of the simulated GIUH runoff hydrograph was also conducted. The GIUH model generated UH with smaller peak discharge Qp, also slower and longer of tp and tb values than the observed UH. Accuracy test of the simulated GIUH runoff hydrograph using Nash-Sutcliffe Efficiency (NSE) shows that Keduang watershed gives a satisfying result, while Wiroko watershed gives less satisfactory result. The inaccuracies occur due to limited flood events used to derive the observed UH and stream tributaries that were not properly modeled based on Strahler method.